2009
DOI: 10.1016/j.ultrasmedbio.2009.06.1093
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone-Tendon Junction Healing Using Water Jet Ultrasound Indentation Method

Abstract: 26The re-establishment of bone-tendon junction (BTJ) tissues with the junction, 27 characterized as a unique transitional fibrocartilage zone, is involved in many trauma and 28 reconstructive surgeries. Experimental and clinical findings have shown that a direct BTJ 29 repair requires a long period of immobilization which may be associated with a 30 postoperative weak knee. Therefore, it's very necessary to evaluate the morphological 31 and mechanical properties of BTJ tissues in situ to better understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Ultrasound imaging and water-jet ultrasound indentation test were performed to measure the thickness and stiffness of emu femoral head cartilage using our established protocol (Supplementary text) [26,27]. Briefly, the thickness of the cartilage was calculated by averaging the distance of cartilage to the subchondral bone on three images obtained by B-mode ultrasound scanning ( Supplementary Fig.…”
Section: Ultrasound Imaging and Indentation Testmentioning
confidence: 99%
“…Ultrasound imaging and water-jet ultrasound indentation test were performed to measure the thickness and stiffness of emu femoral head cartilage using our established protocol (Supplementary text) [26,27]. Briefly, the thickness of the cartilage was calculated by averaging the distance of cartilage to the subchondral bone on three images obtained by B-mode ultrasound scanning ( Supplementary Fig.…”
Section: Ultrasound Imaging and Indentation Testmentioning
confidence: 99%
“…Phantom tests showed that this system was capable of measuring the soft tissue elasticity quantitatively and reliably and also providing a fast C-scan mapping of the tissue elasticity. It was further applied for the study of cartilage degeneration in a bovine patella model [39] and bone-tendon junction healing in a rabbit model [40] in vitro. The noncontact fluid indentation method also has the advantage of lowering the potential or risk of causing damage to the tested soft tissue, especially in tissues such as in scars or wounds where the contact indenter may cause inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…This force can cause breast deformation, which may affect the annotation results. Different methods have been proposed to solve the problem of soft tissue deformation (Crum et al 2004;Gee et al 2003;Guo et al 2006;Khallaghi et al 2012;Krucker et al 2002;Leung et al 2009;Lu et al 2009aLu et al , 2009bTreece et al 2002;Xiao et al 2002). One approach is the use of non-rigid registration methods (Crum et al 2004;Guo et al 2006;Leung et al 2009).…”
Section: Discussionmentioning
confidence: 99%